2020
DOI: 10.1007/s00251-020-01172-8
|View full text |Cite
|
Sign up to set email alerts
|

Specific amino acid patterns define split specificities of HLA-B15 antigens enabling conversion from DNA-based typing to serological equivalents

Abstract: The HLA-B15 typing by serological approaches defined the serological subgroups (or splits) B62, B63, B75, B76, B77 and B70 (B71 and B72). The scarcity of sera with specific anti-HLA antibodies makes the serological typing method difficult to discriminate a high variety of HLA antigens, especially between the B15 antigen subgroups. Advancements in DNA-based technologies have led to a switch from serological typing to high-resolution DNA typing methods. DNA sequencing techniques assign B15 specificity to all all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…The other differences were observed in outlier alleles. For example, the alleles HLA-B*15:46, -B*15:53, -B*15:106, -B*15:212, and -B*15:525 were not previously assigned to any broad HLA-B15 serotypes, 74 on the other hand, these alleles were assigned as B4005 in the present study. The allele HLA-B*15:46 was assigned as HLA-B72 in the HLA Dictionary 2008, but carries a mismatch at residue 45 K compared with the serotype HLA-B72 (45E).…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…The other differences were observed in outlier alleles. For example, the alleles HLA-B*15:46, -B*15:53, -B*15:106, -B*15:212, and -B*15:525 were not previously assigned to any broad HLA-B15 serotypes, 74 on the other hand, these alleles were assigned as B4005 in the present study. The allele HLA-B*15:46 was assigned as HLA-B72 in the HLA Dictionary 2008, but carries a mismatch at residue 45 K compared with the serotype HLA-B72 (45E).…”
Section: Discussioncontrasting
confidence: 48%
“…A comprehensive evaluation of the splits corresponding to the HLA-B*15 alleles was performed in the present study; the results were concordant with those reported in a recent publication from Duygu and collaborators. 74 In both studies, similar sets of residues were used to define the broad HLA-B15 and -B70 serotypes except for residues 24 and 77 that were used for HLA-C serotypes in the present study, and residue 163 that was not used by Duygu and collaborators (Table 3C). Supplemental Table 11 contains 41 HLA-B*15 alleles that were discussed by Duygu and collaborators 74 and the serotype assignments in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations